Boom to bust, ashes to (coal) dust: the contested ethics of energy exchanges in a declining US coal market. (12th March 2019) - Smith, Jessica M.
Abstract: This essay explores how rank‐and‐file producers of energy evaluate the ethics of energy exchanges, which sheds light on some of the unexamined assumptions animating anthropological studies of energy and ethics. Exploring how coal miners experience a massive downturn in Wyoming, the centre of US coal production, reveals differing logics of exchange between the producers and consumers of electricity. Most Americans engage with electricity as consumers through a commodity framework, paying utility companies a fee to purchase kilowatt hours that are abstracted from their productive origins. In contrast, the miners experience energy as more of a gift exchange, keeping in view the network of the ultimate consumers of the coal they produce. These differing logics of exchange entail different ethical obligations in the face of the termination of those relationships as the country moves away from coal‐fired electricity, helping to explain the outrage that was felt in 'coal country' – an outrage that Donald Trump exploited for political purposes during the 2016 US presidential election.